Respuesta :
Answer:
The correct option is C.
Step-by-step explanation:
The given equation is
[tex]x^2+6x=-7[/tex]
If expression is defined as [tex]x^2+bx[/tex], then we add [tex](\frac{-b}{2})^2[/tex] to make it perfect square.
It the given equation b=6, so we will add
[tex](\frac{6}{2})^2=3^2=9[/tex]
Now add 9 on the both sides.
[tex]x^2+6x+9=-7+9[/tex]
[tex](x+3)^2=2[/tex]
[tex]x+3=\pm \sqrt{2}[/tex]
[tex]x=-3\pm \sqrt{2}[/tex]
[tex]x=-3+\sqrt{2},-3-\sqrt{2}[/tex]
[tex]x=-1.59,-4.41[/tex]
The solutions of the given equation are -4.41 and -1.59.
Therefore option C is correct.